FAKTOR-FAKTOR YANG MEMPENGARUHI RENTABILITAS PADA BPR DI KABUPATEN BLORA (Students' Journal of Accounting and Banking, 2013)
This aim of this research is to examine the influance of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating Expanse to Operational Earnings (OEOE), Non Performing Loan (NPL) to the charge of Rentability wich is proxy by Return On Assets (ROA). This research uses purposive sampling method and three banks which is comply with the criteria. During research period show as data research was normally distributed. Besed on multicolineary test, heteroscedasticity test and autocorrelation test variable digressing of classic assumption has not founded, its indicate that the available data has fulfill the condition to use multi linier regression model. Based on testing performed all the classical assumptions show the result of regression equation has assumption of normality, noproblem multikolonieritas, heterocedastity and autocorrelation. The result of analysis with t-statistical test showed that partially LDR have an positive significant impact on ROA with a significance level less than 0,05 (0,004). BOPO have an negative significant impact on ROA with a significance level less than 0,05 (0,000). While CAR, and NPL doesn’t significantly with each level of significance 0,050 and 0,535 greater than 0,05.Simultaneously based on test result of the F-Statistic variable CAR, LDR, BOPO, and NPL proved significant effect on ROA banks at significance level of 0,000 less than 0,05. Adjusted R2 value 0f 0,51 indicates predictive ability of thefive variables on ROA is 51% and the remaining 49% influence by other factors beyond the research model. Keywords: Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating Expanse to Operational Earnings (OEOE), Non Performing Loan (NPL) and Return on Asets (ROA).